(untitled) (World Economics and Finance Bulletin, 2022)
The research aims to measure the effect of free cash flow on the efficiency of investment decisions and their reflection on the value of the firm. The free and efficient investment decisions in the value of the firm, based on the data of the annual financial reports for a sample of the Iraqi companies listed in the Iraqi Stock Exchange, which numbered (27) companies, represented by (15) companies from the banking sector and (8) companies from the industrial sector and (4) A firm from the insurance sector for the period from (2011- 2020). For the purpose of measuring free cash flow, the (Brigham & Houston, 2019) model was used, and the (Richardson, 2006) model was used to measure the efficiency of investment decisions. Using the statistical program (SPAS) to find out the size of the effect between the research variables